A Review of Mendelian Randomization: Assumptions, Methods, and Application to Obesity-Related Diseases - Seungjae Lee; Woojoo Lee (Journal of Obesity & Metabolic Syndrome)
Mendelian randomization (MR) is a statistical method that uses genetic variants as instrumental variables to estimate the causal effect of exposure on an outcome in the presence of unmeasured confounding. In this review, we argue that it is crucial to acknowledge the instrumental variable assumptions in MR analysis. We describe widely used MR methods, using an example from obesity-related metabolic disorders. We describe situations in which instrumental variable assumptions are violated and explain how to evaluate these violations and employ robust methods for accommodating such violations.